Teaching healthy lifestyle behaviors based on philosophical thinking to preschool children: a randomized controlled trial - Zakieh Khoramaki; Mahin Nazari; Leila Ghahremani; Mohammad Hossein Kaveh; Abdolrahim Asadollahi (BMC Public Health)
Abstract Background The promotion of a healthy lifestyle among preschool children is essential for establishing their future habits. Evidence indicates that the incorporation of philosophical thinking—encompassing critical, creative, and compassionate thought—can significantly contribute to children’s cognitive and moral growth, thereby positively affecting their health-related decisions. This research evaluated the effects of imparting healthy lifestyle practices through philosophical thinking to preschool children. Methods This randomized controlled trial involved 120 preschoolers, who were randomly assigned to intervention groups for children, parents, and a control group. Educational sessions were conducted in the intervention groups of preschool children and parents using various educational tools such as films, narratives, and games. Data analysis was performed using SPSS and JAMOVI software. Results The present study provides evidence that instruction in healthy lifestyle behaviors grounded in philosophical thinking significantly enhances the healthy lifestyle practices of preschool children and their parents. The statistical analyses indicate that the improvements achieved are statistically significant, with both children and parents demonstrating enhancements in healthy lifestyle behavior scores two and four months following the intervention. While the effect sizes may be relatively small, the significance of the results underscores the potential for philosophical thinking interventions to foster positive behavior changes over time. Conclusions This research showed that teaching healthy lifestyle practices through philosophical thinking improved healthy behaviors in preschool-aged children. The results were more pronounced in children than in their parents. Future studies should focus on longer interventions and explore the effects across different age groups. Trial registration The international trial code is IRCT20230703058651N1 (date of registration 03/07/2023).